Computational Design of Gas Sensors Based on V3S4 Monolayer - Ilya V. Chepkasov; Ekaterina V. Sukhanova; Alexander G. Kvashnin; Hayk A. Zakaryan; Misha A. Aghamalyan; Yevgeni Sh. Mamasakhlisov; Anton M. Manakhov; Zakhar I. Popov; Dmitry G. Kvashnin (Nanomaterials, 2022)
Novel magnetic gas sensors are characterized by extremely high efficiency and low energy consumption, therefore, a search for a two-dimensional material suitable for room temperature magnetic gas sensors is a critical task for modern materials scientists. Here, we computationally discovered a novel ultrathin two-dimensional antiferromagnet V3S4, which, in addition to stability and remarkable electronic properties, demonstrates a great potential to be applied in magnetic gas sensing devices. Quantum-mechanical calculations within the DFT + U approach show the antiferromagnetic ground state of V3S4, which exhibits semiconducting electronic properties with a band gap of 0.36 eV. A study of electronic and magnetic response to the adsorption of various gas agents showed pronounced changes in properties with respect to the adsorption of NH3, NO2, O2, and NO molecules on the surface. The calculated energies of adsorption of these molecules were −1.25, −0.91, −0.59, and −0.93 eV, respectively. Obtained results showed the prospective for V3S4 to be used as effective sensing materials to detect NO2 and NO, for their capture, and for catalytic applications in which it is required to lower the dissociation energy of O2, for example, in oxygen reduction reactions. The sensing and reducing of NO2 and NO have great importance for improving environmental protection and sustainable development.